Fuzzy Multi Attribute Decision Making Determining House DSS - Gustaf, TuesdaySaka (Universitas PGRI Adi Buana Surabaya, 2024)
The property industry in Indonesia is experiencing rapid development along with improving economic conditions, causing consumers to face difficulties in choosing a house that suits their preferences. Various factors such as price, location, facilities, and payment methods often make decisions complex.The Fuzzy Multi Attribute Decision Making (FMADM) method is used to determine and evaluate the best options based on the degree of suitability of all criteria, with ranking carried out using the defuzzy method. The results of this study are expected to provide practical solutions for consumers in choosing a house that suits their needs and improve the quality of property developer services in Indonesia. The author's test results show that 72% of users feel helped by this solution method.